Neuropsychological functioning in late-life depression - Dybedal, Gro S.; Tanum, Lars; Sundet, Kjetil; Gaarden, Torfinn L.; Bjølseth, Tor M. (Frontiers in Psychology, 2013)
Background: The literature describing neurocognitive function in patients with late-life depression (LLD) show inconsistent findings in regard to incidence and main deficits. Reduced information processing speed is in some studies found to explain deficits in higher order cognitive function, while other studies report specific deficits in memory and executive function. Our aim was to determine the characteristics of neuropsychological functioning in non-demented LLD patients. Methods; A comprehensive neuropsychological battery was administered to a group of hospitalized LLD patients and healthy control subjects. Thirty-nine patients without dementia, 60 years or older meeting DSM-IV criteria for current episode of major depression, and 18 nondepressed control subjects were included. The patient group was characterized by having a long lasting current depressive episode of late-onset depression and by being non-responders to treatment with antidepressants. Neurocognitive scores were calculated for the domains of information processing speed, verbal memory, visuospatial memory, executive function, and language. Number of impairments (performance below the 10th percentile of the control group per domain) for each participant was calculated. Results: Nearly half of the patients had a clinically significant cognitive impairment in at least one neurocognitive domain. Relative to healthy control subjects, LLD patients performed significantly poorer in the domains of information processing speed and executive function. Executive abilities were most frequently impaired in the patient group (39 % of the patients). Even when controlling for differences in processing speed, patients showed more executive deficits than controls. CONCLUSIONS: Controlling for processing speed, patients still showed impaired executive function compared to healthy controls. Reduced executive function thus appears to be the core neurocognitive deficit in LLD. Executive function seems to be an